The Impact of Leadership Styles on the Entrepreneurial Orientation of Small and Medium Enterprises in South Africa - Obey Dzomonda; Olawale Fatoki; Olabanji Oni (Journal of Economics and Behavioral Studies, 2017)
The critical role Small and Medium Enterprises play in the economic prosperity of nations cannot be understated. SMEs actively contribute towards economic growth and development through their active role as innovators and agents for change. The authors of this paper believe that leadership styles exercised by SME owners have a bearing on the innovative ability of SMEs. Hence, this paper aimed at investigating the impact of leadership styles on the entrepreneurial orientation of SMEs in Polokwane Municipality. A quantitative research method was used and 103 SMEs participated in the survey. The random sampling technique was used. Self-administered questionnaires were utilised to collect data in a survey. Data analysis included descriptive statistics, Pearson’s correlation and regression analysis. Reliability of the data collection instruments was measured using the Cronbach’s alpha. The results indicated that the SMEs display average levels of entrepreneurial orientation. In addition, the results showed that SMEs display average levels of leadership styles inclined towards transformational leadership style. Furthermore, the results showed a significant positive relationship between the independent variables: leadership styles with the dependent variable (EO) of SMEs. SMEs were recommended to provide flexible leadership styles that will make EO to flourish in their businesses. Furthermore, the policy makers and relevant authorities were recommended to devise and implement a consortium of strategies and policies that can increase the level of entrepreneurial orientation among SMEs in South Africa.